Investigative analysis of extended-spectrum beta-lactamase (ESBL) producing Pseudomonas aeruginosa isolated from hospitals of Islamabad-Rawalpindi (Journal of Fatima Jinnah Medical University, 2022)
Background: Pseudomonas aeruginosa (P. aeruginosa) is a ubiquitous gram-negative rod shaped bacteria and a significant nosocomial opportunistic pathogen. Current study aimed at the investigation and determination of extended-spectrum beta-lactamase (ESBL) positive P. aeruginosa from clinical samples.Materials and methods: A total of 150 catheter tubes, pus, blood, and sputum samples were collected from three different hospitals in the twin cities of Rawalpindi and Islamabad. The isolates were identified by using standard microbiology procedures. Antibiotic susceptibility of the isolates was done through the disc diffusion method as per the protocol given by CLSI guidelines. Phenotypic characterization of ESBL producers was performed by combination disc test (CDT), double disc synergy test (DDST) and through PCR.Results: A total of 77/218 isolates were identified as P. aeruginosa. Among them 47 were resistant to different drugs, while 28 were identified as multidrug resistant. They were resistant to 9 different drugs including Cefotaxime (49%), Cefipime (41%), Cephradine (32%), Cefotetan (62%), Azetronam (50%), Cofaclor (42%), Ticarcillin (57%), Ciproflaxacin (45%), and Imipenem (36%). CDT and DDST showed that 7/29 isolates produce ESBL. One isolate was positive for VEB and 3 were positive for SHV ESBL genotype.Conclusion: The phenomenon of ESBL production does not only remain in Klebsiella pneumonia and Escherichia coli but could also be found in P. aeruginosa. Moreover, SHV genotype is prevalent in local isolates of P. aeruginosa.
Keywords: Extended-spectrum beta-lactamases; Multiple-drug resistance; Double disc synergy test; Combination disc test